Assessing the Effect of Project-Based Learning on Managerial Skills in Relation to Student Creativity - Falah, Apria Nur Eka; Soeryanto, Soeryanto; Agung, Achmad Imam; Rijanto, Tri; Pramono, Aditya (Department of Electronic and Informatic Engineering Education, Faculty of Engineering, UNY, 2024)
Enhancing managerial skills and creativity is crucial for students in technical fields in the rapidly evolving industry. This study explores the impact of project-based learning (PBL) on students' managerial skills and creativity in CNC machining engineering. The research employs a factorial exposure design, focusing on three key variables: project-based learning as the independent variable, managerial skills as the dependent variable, and creativity as a mediating variable. Data were collected using a Likert scale and analyzed through linear regression techniques. The research involved two classes from grade 11 in the machining engineering department of SMK YPI Darussalam 1 Cerme, which engaged in PBL activities. The findings reveal that project-based learning significantly influences students' managerial skills and creativity. While PBL's effect on managerial skills remains substantial, even when creativity is considered a mediating variable, creativity itself does not significantly mediate this relationship. This suggests that while PBL effectively enhances managerial abilities, it also promotes creativity in students, contributing to a richer educational experience. These results highlight the effectiveness of PBL as a pedagogical approach in the CNC machining curriculum. Although creativity does not moderate the relationship between PBL and managerial skills, PBL is valuable in developing both technical skills and creative potential, thus preparing students to meet future industry challenges effectively.